Application of R-plasmid DNA's from Escherichia coli minicells in genetic transformation - Nesvera, J; Hochmannová, J; Stokrová, J (Folia microbiologica, 1978)
Components of minicell lyzates of Escherichia coli P678.54 (R1 drd 19) and escherichia coli P678.54 (R6K) were visualized in an electron microscope and used for the transformation of Escherichia coli JC7623. The frequency of the resulting transformants (of the order of 10(-6)%) was not appreciably influenced by the manner of lyzate preparation. The presence of covalently closed circular DNA was detected in two different transformants using radioisotopes, thus demonstrating an autonomous existence of R1 drd 19 or R6K plasmids in tested transformants. This finding corresponds with the results of their genetic analysis.
Keywords: molekulová hmotnost; Chloramphenicol; chloramfenikol; R-plasmidy; DNA bakterií; bakteriální transformace; ampicilin; Ampicillin; Escherichia coli; DNA, Bacterial; R Factors; DNA, Circular; kruhová DNA; Transformation, Bacterial; Molecular Weight